1984
DOI: 10.1007/bf00402007
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a heat-labile cellular nuclease in Staphylococcus aureus with properties similar to the extracellular nuclease (EC 3.1.4.7)

Abstract: Besides the well-known heat-stable extracellular staphylococcal nuclease (EC 3.1.4.7) and cell surface bound nuclease, one more nuclease, which is heat-labile, has been identified and purified on phosphorylated cellulose column and characterized. Analyses by Sephadex G-75 gel chromatography indicates that the heat-labile cellular nuclease has molecular weight of about 16,000 similar to those of extracellular and cell-surface bound nucleases. Like the heat-stable nucleases, the heat-labile enzyme acts on both D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Its structure-function aspects have been extensively studied (1,2,16). In addition to the extracellular nuclease, S. aureus also contains intracellular nucleases (12,20). Apparently, these nucleases show many properties common to the extracellular enzyme, implying a precursor-product relationship.…”
mentioning
confidence: 99%
“…Its structure-function aspects have been extensively studied (1,2,16). In addition to the extracellular nuclease, S. aureus also contains intracellular nucleases (12,20). Apparently, these nucleases show many properties common to the extracellular enzyme, implying a precursor-product relationship.…”
mentioning
confidence: 99%
“…The heat-stable nuclease is not the only nuclease produced by 5. aureus. Vakil et al found a heat-labile cellular nuclease which shares a number of properties with the heat-stable nuclease (221). In comparison, the heat-stable nuclease is stable to heating at 100°C for IS minutes whereas the heat-labile nuclease is inactivated within 5 minutes of treatment.…”
Section: Nonspecific Bacterial Nucleasesmentioning
confidence: 99%
“…In comparison, the heat-stable nuclease is stable to heating at 100°C for IS minutes whereas the heat-labile nuclease is inactivated within 5 minutes of treatment. Both enzymes are monomers, prefer heat-denatured DNA as a substrate but can also use RNA as a substrate, have a pH optimum of approximately 10, have a temperature optimum in the range of 45°C to 50°C, and have an absolute requirement for Ca^* ions which could not be substituted by other monovalent or divalent cations (221). Both the heat stable and heat labile nucleases are relatively inactive at pH 7.0 and only have moderate activity at 37°C.…”
Section: Nonspecific Bacterial Nucleasesmentioning
confidence: 99%
See 1 more Smart Citation